A Curious Case of MRSA Bacteremia and Septic Pulmonary Embolism Secondary to Peripheral Venous Catheter. (9th April 2021) - Twito, Joshua; Sahra, Syeda; Jahangir, Abdullah; Mobarakai, Neville
Abstract : Background . Central venous catheters (CVCs) have been frequently associated with septic thrombophlebitis, bacteremia, and septic emboli. Right-sided infective endocarditis is seen concurrently in patients with septic pulmonary emboli. A case of methicillin-resistant Staphylococcus aureus (MRSA) bacteremia and septic pulmonary emboli secondary to infected peripheral venous catheter (PVC) is reported. Transesophageal echocardiogram (TEE) showed no evidence of infective endocarditis. Case Presentation . A 44-year-old female presented to E.R. with left upper extremity pain and swelling at the previously inserted peripheral 18-gauge intravenous catheter site. She also had chest pain, which worsened with inspiration. The patient was found to be in septic shock. Her clinical condition deteriorated acutely. Right upper extremity deep venous thrombosis (DVT) and pulmonary emboli were seen on imaging. Blood cultures grew MRSA. Transthoracic and transesophageal echocardiograms showed no vegetations. The patient responded well to appropriate antibiotics and anticoagulation. Conclusion . Peripherally inserted catheters are an important portal for pathogen entry and need periodic site assessment and frequent evaluation of their need for insertion. Septic pulmonary emboli can also be seen without any evidence of right-sided infective endocarditis.